2011
DOI: 10.1007/s00216-011-5109-x
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific protein glycosylation analysis with glycan isomer differentiation

Abstract: Glycosylation is one of the most common yet diverse post-translational modifications. Information on glycan heterogeneity and glycosite occupancy is increasingly recognized as crucial to understanding glycoprotein structure and function. Yet, no approach currently exists with which to holistically consider both the proteomic and glycomic aspects of a system. Here, we developed a novel method of comprehensive glycosite profiling using nanoflow liquid chromatography/mass spectrometry (nano-LC/MS) that shows glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 37 publications
(61 reference statements)
1
108
0
1
Order By: Relevance
“…The analysis of site-specific microheterogeneity on a protein with multiple N-glycosylation sites in cell or tissue-derived extracts requires more elaborate analytical methods that have become available only recently (16,17,(34)(35)(36). Few studies have shown the relation between protein primary sequence and the observed glycan profile.…”
mentioning
confidence: 99%
“…The analysis of site-specific microheterogeneity on a protein with multiple N-glycosylation sites in cell or tissue-derived extracts requires more elaborate analytical methods that have become available only recently (16,17,(34)(35)(36). Few studies have shown the relation between protein primary sequence and the observed glycan profile.…”
mentioning
confidence: 99%
“…More than 10 distinct types of oligosaccharides are usually identified at a single site (30). Meanwhile, site-specific N-glycosylation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Gradient (300 nL/min) ACN/water/HFo Sproß et al (2013) et al, 2012; Shi et al, 2012;Hua et al, 2012;Su et al, 2015;Parker et al, 2013;Wang et al, 2015) or 2D polyacrylamide gel electrophoresis (PAGE) followed by in-gel digestion (Rogeberg et al, 2013;. Because this type of enzymatic digestion may require very long reaction times, a recent alternative is the employment of in-column immobilized enzymatic reactors for rapid digestion (seconds to minutes), coupled with a 2D analytical system (Xia et al, 2012;Sproß et al, 2013).…”
Section: Ms (Q-tof and Orbitrap)mentioning
confidence: 99%
“…Furthermore, the use of an online 2D nano-LC-chip has been described on several occasions (Delporte et al, 2015;Hua et al, 2012). …”
Section: Ms (Q-tof and Orbitrap)mentioning
confidence: 99%